A comparison of brand equity strength across consumer segments and markets. Issue 5 (21st August 2017) - Stocchi, Lara; Fuller, Rachel
Abstract : Purpose: This paper aims to compare brand equity strength, i.e. the extent to which brand awareness and brand image contribute to purchase propensity, for different segments of consumers (non-users, light users and heavy users) and two different markets (soft drinks and banking, representing a repertoire and a subscription context, respectively). Design/methodology/approach: This aim is pursued using a scalable customer-based brand equity (CBBE) framework, which captures how brand awareness and brand image, on a continuum of brand knowledge, underpin purchase propensity. The framework constitutes a "tool" for the analysis of brand equity strength, and it is applied, alongside a suite of empirical tests, to a large set of longitudinal consumer survey data collected from the same consumers and for both markets. Findings: There are meaningful differences across the three consumer segments considered, especially in relation to brand image values, which are generally greater for more loyal consumers. Furthermore, the overall strength of brand equity is greater for banking brands compared to soft drinks brands. Practical implications: This research highlights the practical importance of detecting and managing differences in brand equity strength across consumer segments with dissimilar brand loyalty. It also suggests that there is relatively more value in evaluating and managing the CBBE process in subscription markets, than in repertoire markets. Originality/value: The contribution of this research to brand equity knowledge is twofold. It addresses concerns in relation to the need to analyze brand equity at a disaggregated level and it sheds light on inconclusive findings in relation to the generalizability of CBBE principles across different types of markets.